Curcumin-like compounds designed to modify amyloid beta peptide aggregation patterns. Issue 50 (21st June 2017) - Battisti, Antonella; Palumbo Piccionello, Antonio; Sgarbossa, Antonella; Vilasi, Silvia; Ricci, Caterina; Ghetti, Francesco; Spinozzi, Francesco; Marino Gammazza, Antonella; Giacalone, Valentina; Martorana, Annamaria; Lauria, Antonino; Ferrero, Claudio; et al.
Abstract : This study suggests new concepts and potential difficulties in the design of novel drugs against diverse amyloidoses, including Alzheimer's disease. Abstract : Curcumin is a natural polyphenol able to bind the amyloid beta peptide, which is related to Alzheimer's disease, and modify its self-assembly pathway. This paper focuses on a multi-disciplinary study that starts from the design of curcumin-like compounds with the key chemical features required for inhibiting amyloid beta aggregation, and reports the effects of these compounds on the in vitro aggregation of amyloid beta peptides. Chemoinformatic screening was performed through the calculation of molecular descriptors that were able to highlight the drug-like profile, followed by docking studies with an amyloid beta peptide fibril. The computational design underlined two different scaffolds that were easily synthesized in good yields. In vitro experiments, ranging from fluorescence spectroscopy and confocal microscopy up to small angle X-ray scattering, provided evidence that the synthesized compounds are able to modify the aggregation pattern of amyloid beta peptides both in the secondary structures, and in terms of the overall structure dimensions. The cytotoxic potential of the synthesized compounds was finally tested in vitro with a model neuronal cell line (LAN5). The overall view of this study suggests new concepts and potential difficulties in the design of novel drugs against diverse amyloidoses, including Alzheimer's disease.